Identification of Nymphal Instars of Mecidea major Sailer and Mecidea minor Ruckes (Hemiptera: Heteroptera: Pentatomidae: Mecideini) from the Southwestern and Central United States - Mcpherson, J. E.; Bundy, C. Scott (Zootaxa, 2021)
The mecideine stink bug genus Mecidea is represented in America north of Mexico by three species: Mecidea major Sailor, Mecidea minor Ruckes, and Mecidea longula Stål. M. major and M. minor are widely distributed, occurring collectively from the Midwest to California. M. longula is known only from south Florida. The life histories of M. major and M. minor have been published including laboratory rearing from egg to adult and descriptions of the immature stages. However, no key has been developed for identification of the nymphs of these two species. Here, we present a key to the nymphs of these taxa to the species and instar levels.